Aluminum nitride ceramic as well as preparation method and application thereof
By using a layered pressing and sintering technology of aluminum nitride mixture and diamond in aluminum nitride ceramics, the problem of difficulty in removing the secondary phase after sintering additives is solved, and the thermal conductivity and density of the ceramics are significantly improved, making it suitable for efficient heat dissipation materials for electronic devices.
Patent Information
- Application Number
- CN202411949386.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2044-12-27
AI Technical Summary
The secondary phase generated by the existing aluminum nitride ceramics after adding sintering aids is difficult to remove, affecting their thermal conductivity.
The combination of aluminum nitride mixture and diamond is used to form the liquid phase of yttrium aluminate by layering pressing and sintering technology, through layering pressing and sintering, the reaction of yttrium oxide and aluminum nitride is used to generate the liquid phase of yttrium aluminate, which promotes densification and purifies the crystal lattice, and at the same time, diamond improves the secondary phase problem.
Effectively eliminate the secondary phase, improve the thermal conductivity and density of aluminum nitride ceramics, and enhance its application performance in electronic devices.
Smart Images

Figure BDA0005214490710000141 
Figure BDA0005214490710000151
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of ceramic materials, and in particular to an aluminum nitride ceramic and a preparation method and application thereof. Background Art
[0002] As electronic products become more multifunctional, intelligent, and miniaturized, the integration of electronic substrates is becoming increasingly high. The large amount of heat generated inside the device during operation is difficult to dissipate in a short period of time. The long-term operation of electronic devices at high temperatures will not only affect normal operation, but will even shorten their service life. Therefore, high heat dissipation substrates are urgently needed to solve this problem. Aluminum nitride ceramics have attracted much attention due to their high thermal conductivity, low dielectric constant, low dielectric loss, linear expansion coefficient matching that of semiconductor materials such as silicon, high insulation, and high mechanical strength, becoming the first choice for insulating heat dissipation packaging materials and semiconductor substrate materials.
[0003] However, there are also some problems in the preparation process of aluminum nitride ceramics: 1) Due to the characteristics of aluminum nitride as a strong covalent compound, small self-diffusion coefficient, and high melting point, it is difficult to sinter to a dense state; 2) Due to the presence of the surface oxide film, oxygen atoms are easily dissolved into the aluminum nitride lattice and produce aluminum vacancies, thereby aggravating phonon scattering and reducing the thermal conductivity of aluminum nitride. Based on this, the method of adding sintering aids or component doping is widely used to obtain ceramics with high thermal conductivity. Commonly used sintering aids are rare earth or alkaline earth oxides and fluorides (such as Y2O3, YF3, CaO, CaF2, etc.). The low-melting-point sintering aids themselves melt to produce a liquid phase or react with aluminum oxide on the surface of aluminum nitride to produce a liquid phase, accelerate mass transfer, and achieve the effect of reducing the temperature required for densification and purifying the aluminum nitride lattice; however, after adding the sintering aid, there will be a problem that the residual secondary phase generated is difficult to remove, and a large amount of residual secondary phase will directly affect the thermal conductivity of the ceramic material.
[0004] In view of this, it is indeed necessary to provide a technical solution to the above problems. Summary of the invention
[0005] One of the purposes of the present invention is to provide an aluminum nitride ceramic in view of the deficiencies of the prior art, so as to improve the secondary phase problem generated by the current aluminum nitride ceramic after adding a sintering aid, and ensure the thermal conductivity of the aluminum nitride ceramic.
[0006] In order to achieve the above object, the present invention adopts the following technical solutions:
[0007] An aluminum nitride ceramic comprises an aluminum nitride mixture and diamond, wherein the aluminum nitride mixture comprises aluminum nitride and yttrium oxide, wherein the mass ratio of the aluminum nitride mixture to the diamond is (12-18):(1.6-4), and the mass content of yttrium oxide is 1%-5% of the total mass of the aluminum nitride mixture.
[0008] Preferably, the mass ratio of the aluminum nitride mixture to diamond is (12-18):(2.4-3.2); the particle size D50 of the aluminum nitride powder is 1 μm-3 μm, and the particle size D50 of the yttrium oxide powder is 1 μm-3 μm.
[0009] A second object of the present invention is to provide a method for preparing aluminum nitride ceramics, comprising the following steps:
[0010] S1, mixing aluminum nitride and yttrium oxide, and pressing to form a first mixed layer;
[0011] S2, laying diamond powder on the upper surface of the first mixed layer, and pressing to form a first diamond layer;
[0012] S3, continuing to lay a mixture of aluminum nitride and yttrium oxide on the upper surface of the first diamond layer, and pressing to form a second mixed layer;
[0013] S4, repeating step S2 and step S3 in sequence, the number of repetitions is 0 to 2 times, to obtain a green billet;
[0014] S5. Sinter the green blank obtained in step S4 at a pressure of 30 to 50 MPa and a temperature of 1600 to 1850° C. in an inert gas atmosphere for 4 to 8 hours, and then cool the mixture to obtain aluminum nitride ceramics.
[0015] Preferably, the pressing pressure of steps S1 to S4 is 30-40 MPa, and the pressing time is 5-10 min. In steps S1 to S4, the total thickness of the diamond layer is 0.4 mm to 1 mm, and the total thickness of the mixed layer is 1.6 mm to 2.4 mm.
[0016] Preferably, step S4 further includes laying boron nitride powder on both sides of the blank.
[0017] Preferably, in step S5, the temperature is heated to 1600° C. to 1850° C. at a heating rate of 10 to 20° C. / min for sintering.
[0018] Preferably, the number of repetitions in step S4 is 1;
[0019] The preparation steps of the green billet are:
[0020] Aluminum nitride and yttrium oxide are mixed and pressed to form a first mixed layer;
[0021] Placing diamond powder on the upper surface of the first mixed layer and pressing to form a first diamond layer;
[0022] A mixture of aluminum nitride and yttrium oxide is continuously laid on the upper surface of the first diamond layer, and pressed to form a second mixed layer;
[0023] Diamond powder is laid on the upper surface of the second mixed layer and pressed to form a second diamond layer;
[0024] A mixture of aluminum nitride and yttrium oxide is continuously laid on the upper surface of the second diamond layer, and pressed to form a third mixed layer to obtain a green blank.
[0025] Preferably, the thickness of the first mixed layer after pressing is a, the thickness of the second mixed layer after pressing is b, the thickness of the third mixed layer after pressing is c, the thickness of the first diamond layer after pressing is m, and the thickness of the second diamond layer after pressing is n, satisfying the following relationship: 0<a≤b, 0<c≤b, 0<m≤b, 0<n≤b.
[0026] Preferably, the value of m or n is independently selected from 0.2 mm to 0.5 mm, the value of b is 0.8 mm to 1.2 mm, and the value of a or c is independently selected from 0.4 mm to 0.6 mm.
[0027] A third object of the present invention is to provide an application of the aluminum nitride ceramic described above or the aluminum nitride ceramic prepared by the preparation method of the aluminum nitride ceramic described above in electronic devices.
[0028] The beneficial effects of the present invention are as follows: the aluminum nitride ceramic provided by the present invention uses yttrium oxide as a sintering aid at a specific content ratio, utilizes the extremely strong affinity of yttrium oxide for oxygen, and the low Gibbs free energy of the reaction between yttrium oxide and aluminum oxide on the surface of aluminum nitride, so that the reaction of aluminum oxide and yttrium oxide can be carried out at a lower temperature, and the generated yttrium aluminate liquid phase accelerates mass transfer and promotes the densification of aluminum nitride; in addition, the generation of the liquid phase causes the surface layer of the aluminum nitride grains to dissolve in the liquid phase, and in the dissolution-precipitation process, it promotes a full reaction between oxygen impurities and the sintering aid, thereby purifying the lattice, thereby improving the thermal conductivity of the aluminum nitride ceramic. At the same time, diamond is added, not only to improve the thermal conductivity of the product by utilizing the extremely high thermal conductivity of diamond itself, but more importantly, diamond can promote the carbon thermal reduction-nitridation reaction of yttrium aluminate, so that the second phase generated by yttrium oxide and aluminum oxide can continue to react in a reducing atmosphere. In this way, the driving force for the migration of the second phase to the surface includes not only physical factors (capillary force) but also chemical factors (transfer of chemical equilibrium). The second phase is more easily eliminated from the grain boundary, and the contact between aluminum nitride grains is closer, thereby further improving the thermal conductivity. DETAILED DESCRIPTION
[0029] In order to make the technical solutions and advantages of the present invention more clear, the present invention and its beneficial effects are described in further detail below, but the embodiments of the present invention are not limited thereto.
[0030] The aluminum nitride ceramic of the present invention can be used as an insulating heat dissipation material and can be applied where electronic devices require it, such as an insulating heat dissipation packaging material or a semiconductor substrate material. Of course, it can also be applied in other fields that require insulation and heat dissipation, which is not limited here.
[0031] The aluminum nitride ceramic comprises an aluminum nitride mixture and diamond, wherein the aluminum nitride mixture comprises aluminum nitride and yttrium oxide, wherein the mass ratio of the aluminum nitride mixture to the diamond is (12-18):(1.6-4), and the mass content of yttrium oxide is 1%-5% of the total mass of the aluminum nitride mixture.
[0032] The aluminum nitride ceramic provided by the present invention utilizes yttrium oxide and diamond as sintering additives at the same time. On the one hand, yttrium oxide can react with aluminum oxide to generate an yttrium aluminate liquid phase, thereby promoting the densification of the sample, purifying the aluminum nitride lattice, and improving the thermal conductivity. On the other hand, diamond is utilized to improve the secondary phase problem generated by the reaction of yttrium oxide and aluminum oxide. At the same time, diamond itself has extremely high thermal conductivity, good insulation and mechanical properties, and can further improve the overall performance of the product.
[0033] Compared with the use of other high thermal conductivity additives (such as graphene), although it can also improve the thermal conductivity of the system, it often brings other effects. For example, graphene will improve the conductivity and affect the insulation performance, and other high thermal conductivity additives cannot solve the secondary phase problem caused by sintering aids. The use of diamond additives can not only ensure the insulation performance of the system, but also the synergistic effect of yttrium oxide and diamond makes the secondary phase content of the prepared aluminum nitride ceramics less and the thermal conductivity is extremely high, which has a good practical application effect.
[0034] In addition, compared with other sintering aids (such as samarium oxide), yttrium oxide and diamond have a synergistic effect. Diamond not only serves as an additive to improve thermal conductivity, but also can improve the secondary phase problem caused by yttrium oxide.
[0035] In order to ensure the various properties of aluminum nitride ceramics, it is equally important to control the content of each raw material.
[0036] Specifically, the mass ratio of aluminum nitride mixture to diamond can be (12-18): (1.6-2.0), (12-18): (2.0-2.4), (12-18): (2.4-2.8), (12-18): (2.8-3.2), (12-18): (3.2-3.6) or (12-18): (3.6-4.0), for example, including but not limited to 12: 1.6, 12: 2.4, 12: 3.2, 15: 1.6, 15: 2.4, 15: 2.8, 15: 3.2, 15: 3.6, 15: 4, 18: 2.4, 18: 4, etc. Preferably, the mass ratio of aluminum nitride mixture to diamond is (12-18): (2.4-3.2).
[0037] The mass content of yttrium oxide can be 1%, 2%, 3%, 4% or 5% of the total mass of the aluminum nitride mixture. Preferably, the mass content of yttrium oxide can be 2% to 4% of the total mass of the aluminum nitride mixture.
[0038] In some embodiments, the particle size D50 of the aluminum nitride powder is 1 μm to 3 μm, specifically 1 μm to 1.5 μm, 1.5 μm to 2 μm, 2 μm to 2.5 μm or 2.5 μm to 3 μm.
[0039] In some embodiments, the particle size D50 of the yttrium oxide powder is 1 μm to 3 μm, and may be specifically 1 μm to 1.5 μm, 1.5 μm to 2 μm, 2 μm to 2.5 μm, or 2.5 μm to 3 μm.
[0040] Relatively fine particles are used for mixing to increase the contact area and allow a more complete reaction between yttrium oxide and oxygen impurities to ensure the purification effect of the aluminum nitride lattice.
[0041] In addition, the present invention also provides a method for preparing aluminum nitride ceramics, comprising the following steps:
[0042] S1, mixing aluminum nitride and yttrium oxide, and pressing to form a first mixed layer;
[0043] S2, laying diamond powder on the upper surface of the first mixed layer, and pressing to form a first diamond layer;
[0044] S3, continuing to lay a mixture of aluminum nitride and yttrium oxide on the upper surface of the first diamond layer, and pressing to form a second mixed layer;
[0045] S4, repeating step S2 and step S3 in sequence, the number of repetitions is 0 to 2 times, to obtain a green billet;
[0046] S5. Sinter the green blank obtained in step S4 at a pressure of 30 to 50 MPa and a temperature of 1600 to 1850° C. in an inert gas atmosphere for 4 to 8 hours, and then cool the mixture to obtain aluminum nitride ceramics.
[0047] The preparation method provided by the present invention can effectively eliminate the problem of secondary phase by adding auxiliary agents yttrium oxide and diamond in combination with the preparation method. Specifically, diamond can promote the carbon thermal reduction-nitridation reaction of yttrium aluminate, so that the second phase generated by yttrium oxide and aluminum oxide can continue to react in a reducing atmosphere, and the design of the diamond layer setting pre-sets the migration direction of the second phase, allowing it to migrate in the direction of diamond. In this way, the driving force for the migration of the second phase to the surface is not only the original physical factor (capillary force), but also includes chemical factors (transfer of chemical equilibrium), thereby making it easier to eliminate the generated second phase from the grain boundary, thereby effectively solving the problem that the secondary phase generated by the current aluminum nitride ceramic after adding the sintering aid is difficult to eliminate. After eliminating the second phase, the contact between the aluminum nitride grains is closer, and the direct contact between the aluminum nitride grains also provides a more direct channel for heat flow diffusion, and the thermal conductivity is further improved.
[0048] After many experimental studies, the inventors found that compared with the preparation method of directly uniformly mixing aluminum nitride powder, yttrium oxide and diamond, although it can also improve the thermal conductivity of fired aluminum nitride ceramics, it still does not solve the problem of secondary phases well, and the improvement effect needs to be improved. To this end, the inventors continued to explore and found that the use of the layered preparation method of the present invention is equivalent to setting the migration direction of the second phase in the system in advance, increasing the driving force for the second phase to migrate to the surface, thereby greatly reducing the second phase remaining at the grain boundary, so that the thermal conductivity of aluminum nitride ceramics is further improved, and the performance of aluminum nitride ceramics is more excellent.
[0049] In addition, to ensure the sintering effect, the inventors conducted experimental research and found that sintering the green billet at a temperature of 1600-1850°C for 4h-8h can ensure the sufficiency of the system reaction, and the secondary phase can migrate more fully, thus ensuring the thermal conductivity of the sample.
[0050] Specifically, the sintering temperature may be 1600-1650°C, 1650-1700°C, 1700-1750°C, 1750-1800°C or 1800-1850°C. Generally speaking, as the sintering temperature increases, the performance of aluminum nitride becomes better. When the temperature is low, the additive does not react fully with aluminum oxide, resulting in a low thermal conductivity and density of the final product. Preferably, the sintering temperature is 1800-1850°C.
[0051] The heat preservation sintering time can be 4h to 5h, 5h to 6h, 6h to 7h or 7h to 8h. As the heat preservation sintering time increases, the density and thermal conductivity of the product will also increase, but based on energy consumption considerations, the heat preservation sintering time is preferably 6h to 8h.
[0052] In some embodiments, the pressing pressure of step S1 to step S4 is 30-40 MPa, and the pressing time is 5-10 min. Pressing under a higher pressure can better ensure the compactness of the green blank at the beginning of sintering, and the migration of the secondary phase to the diamond layer is smoother, thereby having a better effect on eliminating the secondary phase.
[0053] In some embodiments, in step S1 to step S4, the total thickness of the diamond layer is 0.4 mm to 1 mm, and the total thickness of the mixed layer is 1.6 mm to 2.4 mm. The thickness of the diamond layer and the mixed layer is controlled within the above range, while ensuring the thermal conductivity of the aluminum nitride ceramic, it can also ensure its mechanical stability and ensure its application stability in the field of electronic devices.
[0054] In some embodiments, step S4 further includes laying boron nitride powder on both sides of the blank. In order to prevent the graphite in the sintering tool from affecting the product, boron nitride powder is laid on both sides of the blank during the preparation process, thereby preventing the sintering tool from affecting the experiment.
[0055] In some embodiments, in step S5, sintering is performed by heating to 1600°C to 1850°C at a heating rate of 10 to 20°C / min. The inventors have found that as the heating rate increases during the sintering process, the performance of aluminum nitride ceramics tends to decrease. This is because when the heating rate is too fast (such as a heating rate of 20°C / min), the reaction between aluminum nitride and the additive is not sufficient, so the thermal conductivity is low. However, for production cost considerations, it is preferred to heat at a heating rate of 10°C / min, which can save costs and avoid energy waste, and also make the sintered product have excellent performance.
[0056] Specifically, the number of repetitions in step S4 may be 0 to 2 times:
[0057] 1) When the number of repetitions in step S4 is 0, the green blank includes the first mixed layer, the first diamond layer, and the second mixed layer which are arranged in sequence.
[0058] 2) When the number of repetitions in step S4 is 1, the green blank includes a first mixed layer, a first diamond layer, a second mixed layer, a second diamond layer, and a third mixed layer arranged in sequence;
[0059] The preparation steps of the green billet are:
[0060] Aluminum nitride and yttrium oxide are mixed and pressed to form a first mixed layer;
[0061] Placing diamond powder on the upper surface of the first mixed layer and pressing to form a first diamond layer;
[0062] A mixture of aluminum nitride and yttrium oxide is continuously laid on the upper surface of the first diamond layer, and pressed to form a second mixed layer;
[0063] Diamond powder is laid on the upper surface of the second mixed layer and pressed to form a second diamond layer;
[0064] A mixture of aluminum nitride and yttrium oxide is continuously laid on the upper surface of the second diamond layer, and pressed to form a third mixed layer to obtain a green blank.
[0065] 3) When the number of repetitions in step S4 is 2 times, that is, the green blank includes the first mixed layer, the first diamond layer, the second mixed layer, the second diamond layer, the third mixed layer, the third diamond layer, and the fourth mixed layer arranged in sequence, the preparation method can refer to the above description.
[0066] Preferably, the number of repetitions in step S4 is 1. The inventors found that when a five-layer blank design is adopted, on the one hand, diamond layers are set at both ends of the blank, the traction direction of the second phase is more, and both ends can move, and the effect of directional traction of the second phase is better, thereby achieving the purpose of eliminating the residual secondary phase and further improving the density and thermal conductivity of aluminum nitride; on the other hand, the resistance to the migration of the secondary phase will not increase due to too many layers of diamond, but will be detrimental to the elimination of the secondary phase, and too much diamond will also increase the difficulty of processing due to its high hardness.
[0067] In addition, the outermost layer is still stacked with an aluminum nitride mixture. On the one hand, the thermal conductivity of the system is better. On the other hand, when aluminum nitride ceramics are used as electronic substrates, they can be better processed on the ceramic surface, making their application more convenient and more practical.
[0068] For a five-layer blank, the thickness of the first mixed layer after pressing is a, the thickness of the second mixed layer after pressing is b, the thickness of the third mixed layer after pressing is c, the thickness of the first diamond layer after pressing is m, and the thickness of the second diamond layer after pressing is n, then the thickness satisfies the following relationship: 0<a≤b, 0<c≤b, 0<m≤b, 0<n≤b.
[0069] Preferably, the thickness satisfies the following relationship: 0<a<b, 0<c<b, 0<m<b, 0<n<b. Compared with the secondary phase in the second mixed layer that can migrate to both ends, the first mixed layer and the third mixed layer can only migrate to the diamond layer at one end. Therefore, setting the first mixed layer and the third mixed layer of the outer layer to a relatively thinner thickness can more fully ensure the overall density of aluminum nitride, and the thermal conductivity of the product is also better.
[0070] In addition, by also setting the thickness of the first diamond layer and the thickness of the second diamond layer to be lower than the thickness of the second mixed layer, it is possible to avoid the diamond layer being too thick and affecting the migration of the secondary phase.
[0071] In some embodiments, the value of m or n is independently selected from 0.2 mm to 0.5 mm, the value of b is 0.8 mm to 1.2 mm, and the value of a or c is independently selected from 0.4 mm to 0.6 mm.
[0072] Specifically, the thickness m of the first diamond layer can be 0.2mm, 0.3mm, 0.4mm or 0.5mm; the thickness n of the second diamond layer can be 0.2mm, 0.3mm, 0.4mm or 0.5mm; the thickness b of the second mixed layer can be 0.8mm, 0.9mm, 1.0mm, 1.1mm or 1.2mm; the thickness a of the first mixed layer can be 0.4mm, 0.5mm or 0.6mm; the thickness c of the third mixed layer can be 0.4mm, 0.5mm or 0.6mm.
[0073] The present invention and its beneficial effects will be further described in detail below in conjunction with specific embodiments, but the embodiments of the present invention are not limited thereto.
[0074] Example 1
[0075] An aluminum nitride ceramic comprises an aluminum nitride mixture and diamond, wherein the aluminum nitride mixture comprises aluminum nitride and yttrium oxide, wherein the mass ratio of the aluminum nitride mixture to the diamond is 15:2.4, and the mass content of the yttrium oxide is 3% of the total mass of the aluminum nitride mixture; the particle size D50 of the aluminum nitride powder is 2 μm, and the particle size D50 of the yttrium oxide powder is 2 μm.
[0076] The preparation method of the aluminum nitride ceramic is as follows:
[0077] Aluminum nitride and yttrium oxide are mixed according to the above mass ratio. Specifically, 0.9 g of yttrium oxide and 29.1 g of aluminum nitride powder are weighed and placed in a polytetrafluoroethylene tank, and the polytetrafluoroethylene tank is placed on a mixer at 300 r / min and rotated for 12 hours to achieve uniform mixing of the powders;
[0078] 3.75 g of the mixture of aluminum nitride and yttrium oxide was put into a graphite mold and pressed at 30 MPa for 10 min to form a first mixed layer with a thickness of 0.5 mm.
[0079] 1.2 g of diamond powder was laid on the upper surface of the first mixed layer and pressed at 30 MPa for 10 min to form a first diamond layer with a thickness of 0.3 mm;
[0080] 7.5 g of a mixture of aluminum nitride and yttrium oxide is continuously laid on the upper surface of the first diamond layer and pressed at 30 MPa for 10 min to form a second mixed layer having a thickness of 1 mm.
[0081] 1.2 g of diamond powder was laid on the upper surface of the second mixed layer and pressed at 30 MPa for 10 min to form a second diamond layer with a thickness of 0.3 mm.
[0082] 3.75 g of a mixture of aluminum nitride and yttrium oxide was continued to be laid on the upper surface of the second diamond layer, and pressed at 30 MPa for 10 min to form a third mixed layer with a thickness of 0.5 mm to obtain a blank. Boron nitride powder was evenly laid on both sides of the blank to avoid the influence of the graphite mold on the experiment.
[0083] The graphite mold was placed in a hot press furnace in a nitrogen atmosphere, heated to 1850°C at a temperature rise rate of 10°C / min at room temperature at a pressure of 40MPa to sinter the green blank, and sintered at 1850°C for 8 hours, then cooled to room temperature to obtain aluminum nitride ceramics.
[0084] Example 2
[0085] The difference from Example 1 is the thickness of the diamond layer. The thickness of the first diamond layer and the second diamond layer are both 0.2 mm, the corresponding amount of the first diamond layer and the second diamond layer added is 0.8 g, the total amount of diamond added is 1.6 g, and the mass ratio of aluminum nitride mixture to diamond is 15:1.6. The rest can be referred to Example 1, which will not be repeated here.
[0086] Example 3
[0087] The difference from Example 1 is the thickness of the diamond layer. The thickness of the first diamond layer and the second diamond layer are both 0.4 mm, the corresponding amount of the first diamond layer and the second diamond layer added is 1.6 g, the total amount of diamond added is 3.2 g, and the mass ratio of aluminum nitride mixture to diamond is 15:3.2. The rest can be seen in Example 1, which will not be repeated here.
[0088] Example 4
[0089] The difference from Example 1 is the thickness of the diamond layer. The thickness of the first diamond layer and the second diamond layer are both 0.5 mm, the corresponding amount of the first diamond layer and the second diamond layer added is 2 g, the total amount of diamond added is 4 g, and the mass ratio of aluminum nitride mixture to diamond is 15:4. The rest can be seen in Example 1, which will not be repeated here.
[0090] Example 5
[0091] Different from Example 1, the diamond powder addition method of this embodiment does not adopt a layered stacking structure, and aluminum nitride, yttrium oxide and diamond powder are evenly mixed. The sintering method and sintering conditions can refer to Example 1 and will not be repeated here.
[0092] Example 6
[0093] Different from Example 1, the blank of this example is a three-layer structure, including a first mixed layer, a first diamond layer and a second mixed layer, wherein the thickness of the first mixed layer is 1 mm, the thickness of the first diamond layer is 0.6 mm, and the thickness of the second mixed layer is 1 mm. The rest can be referred to Example 1, which will not be repeated here.
[0094] Example 7
[0095] Different from Example 1, the blank of this example is a seven-layer structure, including a first mixed layer, a first diamond layer, a second mixed layer, a second diamond layer, a third mixed layer, a third diamond layer, and a fourth mixed layer, wherein the thickness of the first mixed layer, the second mixed layer, the third mixed layer, and the fourth mixed layer is 0.5 mm, and the thickness of the first diamond layer, the second diamond layer, and the third diamond layer is 0.2 mm. The rest can be referred to Example 1, and will not be repeated here.
[0096] Example 8
[0097] The difference from Example 1 is that the mass content of yttrium oxide in this example is 1% of the total mass of the aluminum nitride mixture. The rest can be found in Example 1 and will not be described again.
[0098] Example 9
[0099] The difference from Example 1 is that the mass content of yttrium oxide in this example is 5% of the total mass of the aluminum nitride mixture. The rest can be found in Example 1 and will not be described again.
[0100] Example 10
[0101] Different from Example 9, the diamond powder addition method of this embodiment does not adopt a layered stacking structure, and aluminum nitride, yttrium oxide and diamond powder are evenly mixed. The sintering method and sintering conditions can be found in Example 9 and will not be repeated here.
[0102] Embodiment 11
[0103] An aluminum nitride ceramic comprises an aluminum nitride mixture and diamond, wherein the aluminum nitride mixture comprises aluminum nitride and yttrium oxide, wherein the mass ratio of the aluminum nitride mixture to the diamond is 12:2.4, the particle size D50 of the aluminum nitride powder is 1 μm, and the particle size D50 of the yttrium oxide powder is 1 μm.
[0104] The preparation method of the aluminum nitride ceramic is as follows:
[0105] Aluminum nitride and yttrium oxide are mixed according to the above mass ratio. Specifically, 0.9 g of yttrium oxide and 29.1 g of aluminum nitride powder are weighed and placed in a polytetrafluoroethylene tank, and the polytetrafluoroethylene tank is placed on a mixer at 300 r / min and rotated for 12 hours to achieve uniform mixing of the powders;
[0106] 3 g of the mixture of aluminum nitride and yttrium oxide was put into a graphite mold and pressed at 40 MPa for 8 min to form a first mixed layer with a thickness of 0.4 mm.
[0107] 1.2 g of diamond powder was laid on the upper surface of the first mixed layer and pressed at 40 MPa for 8 min to form a first diamond layer with a thickness of 0.3 mm;
[0108] 6 g of a mixture of aluminum nitride and yttrium oxide is continuously laid on the upper surface of the first diamond layer, and pressed at 40 MPa for 8 min to form a second mixed layer having a thickness of 0.8 mm;
[0109] 1.2 g of diamond powder was laid on the upper surface of the second mixed layer and pressed at 40 MPa for 8 min to form a second diamond layer with a thickness of 0.3 mm.
[0110] 3 g of a mixture of aluminum nitride and yttrium oxide was continued to be laid on the upper surface of the second diamond layer, and pressed at 40 MPa for 8 min to form a third mixed layer with a thickness of 0.4 mm to obtain a blank. Boron nitride powder was evenly laid on the surrounding side of the blank to avoid the influence of the graphite mold on the experiment.
[0111] The graphite mold was placed in a hot press furnace in a nitrogen atmosphere, heated to 1850°C at a temperature rise rate of 10°C / min at room temperature at a pressure of 40MPa to sinter the green blank, and sintered at 1850°C for 6 hours, then cooled to room temperature to obtain aluminum nitride ceramics.
[0112] Example 12
[0113] An aluminum nitride ceramic comprises an aluminum nitride mixture and diamond, wherein the aluminum nitride mixture comprises aluminum nitride and yttrium oxide, wherein the mass ratio of the aluminum nitride mixture to the diamond is 18:2.4, the particle size D50 of the aluminum nitride powder is 3 μm, and the particle size D50 of the yttrium oxide powder is 3 μm.
[0114] The preparation method of the aluminum nitride ceramic is as follows:
[0115] Aluminum nitride and yttrium oxide are mixed according to the above mass ratio. Specifically, 0.9 g of yttrium oxide and 29.1 g of aluminum nitride powder are weighed and placed in a polytetrafluoroethylene tank, and the polytetrafluoroethylene tank is placed on a mixer at 300 r / min and rotated for 12 hours to achieve uniform mixing of the powders;
[0116] 4.5 g of the mixture of aluminum nitride and yttrium oxide was put into a graphite mold and pressed at 50 MPa for 5 minutes to form a first mixed layer with a thickness of 0.6 mm.
[0117] 1.2 g of diamond powder was laid on the upper surface of the first mixed layer and pressed at 50 MPa for 5 min to form a first diamond layer with a thickness of 0.3 mm;
[0118] 9 g of a mixture of aluminum nitride and yttrium oxide was continuously laid on the upper surface of the first diamond layer, and pressed at 50 MPa for 5 minutes to form a second mixed layer having a thickness of 1.2 mm.
[0119] 1.2 g of diamond powder was laid on the upper surface of the second mixed layer and pressed at 50 MPa for 5 min to form a second diamond layer with a thickness of 0.3 mm.
[0120] 4.5 g of a mixture of aluminum nitride and yttrium oxide was continued to be laid on the upper surface of the second diamond layer, and pressed at 50 MPa for 5 minutes to form a third mixed layer with a thickness of 0.6 mm to obtain a blank. Boron nitride powder was evenly laid on the surrounding side of the blank to avoid the influence of the graphite mold on the experiment.
[0121] The graphite mold was placed in a hot pressing furnace in a nitrogen atmosphere, heated to 1850°C at a temperature rise rate of 10°C / min at room temperature at a pressure of 50MPa to sinter the green blank, and sintered at 1850°C for 8 hours, then cooled to room temperature to obtain aluminum nitride ceramics.
[0122] Embodiment 13
[0123] Different from Example 1, the sintering conditions in the preparation process of the aluminum nitride ceramic are: heating to 1850° C. at a heating rate of 15° C. / min. The rest can be found in Example 1 and will not be repeated here.
[0124] Embodiment 14
[0125] Different from Example 1, the sintering conditions in the preparation process of the aluminum nitride ceramic are: heating to 1850° C. at a heating rate of 20° C. / min. The rest can be referred to Example 1 and will not be repeated here.
[0126] Embodiment 15
[0127] Different from Example 1, the sintering conditions in the preparation process of the aluminum nitride ceramic are: heating to 1600° C. at a heating rate of 10° C. / min. The rest can be found in Example 1 and will not be repeated here.
[0128] Example 16
[0129] Different from Example 1, the sintering conditions in the preparation process of the aluminum nitride ceramic are: heating to 1750° C. at a heating rate of 10° C. / min. The rest can be found in Example 1 and will not be repeated here.
[0130] Embodiment 17
[0131] Different from Example 1, the sintering conditions in the preparation process of the aluminum nitride ceramic are: heating to 1850° C. at a heating rate of 10° C. / min and sintering for 4 hours. The rest can be found in Example 1 and will not be repeated here.
[0132] Embodiment 18
[0133] Different from Example 1, the sintering conditions in the preparation process of the aluminum nitride ceramic are: heating to 1850° C. at a heating rate of 10° C. / min and sintering for 6 hours. The rest can be found in Example 1 and will not be repeated here.
[0134] Comparative Example 1
[0135] The difference from Example 1 is that the sintering aid of this comparative example replaces yttrium oxide with samarium oxide. The rest can be referred to Example 1 and will not be described again.
[0136] Comparative Example 2
[0137] The difference from Example 1 is that the mass ratio of the aluminum nitride mixture to diamond in this comparative example is 15:1.0. The rest can be referred to Example 1 and will not be described again.
[0138] Comparative Example 3
[0139] The difference from Example 1 is that the mass ratio of the aluminum nitride mixture to diamond in this comparative example is 15:7.5. The rest can be referred to Example 1 and will not be described again.
[0140] Comparative Example 4
[0141] Different from Example 1, the sintering conditions in the preparation process of the aluminum nitride ceramic are: heating to 2000° C. at a heating rate of 10° C. / min. The rest can be referred to Example 1 and will not be repeated here.
[0142] The aluminum nitride ceramics obtained in Examples 1 to 18 and Comparative Examples 1 to 4 were subjected to performance tests, including testing the density using the Archimedean drainage method, and using the theoretical density of aluminum nitride as 3.26 g / cm 3 Calculate the relative density. Since components with different densities may be generated during the sintering process, the relative density may be slightly different from the actual density. Use a laser thermal constant analyzer to measure the thermal diffusion coefficient of the product, and calculate its thermal conductivity.
[0143] The test results are shown in Table 1 below.
[0144] Table 1 Aluminum nitride ceramic performance test results
[0145]
[0146]
[0147] From the comparison in Table 1 above, it can be seen that the aluminum nitride ceramic provided by the present invention uses yttrium oxide and diamond as additives. At a certain content, yttrium oxide can better purify the lattice structure, and diamond can improve the secondary phase problem caused by yttrium oxide. In particular, the layered preparation method can effectively improve the density and thermal conductivity of aluminum nitride ceramics.
[0148] Among them, in Comparative Example 1, yttrium oxide is replaced with samarium oxide. Although the density of the ceramic does not change significantly, the thermal conductivity is reduced, which shows that the matching of yttrium oxide-diamond is better than that of samarium oxide-diamond. The diamond content in Comparative Example 2 is reduced, resulting in a significant decrease in thermal conductivity, which is attributed to the fact that the less diamond content cannot effectively promote the carbon thermal reduction-nitridation reaction, and the secondary phase cannot migrate in time at the aluminum nitride grain boundary. In Comparative Example 3, the diamond content is increased. Due to the high thermal conductivity of diamond itself, the thermal conductivity of the ceramic also reaches a higher level. However, due to the mismatch between the thermal expansion coefficients of diamond and semiconductors such as silicon, in practical applications, excessive diamond content will accelerate the mechanical failure of the chip and the ceramic substrate. In Comparative Example 4, the sintering temperature is increased compared to Example 1, but the improvement in thermal conductivity is very small. In addition, the high sintering temperature causes a huge loss of energy. Therefore, the aluminum nitride ceramics prepared by the preparation method of aluminum nitride ceramics adopted in the present invention have excellent performance and will not cause energy waste, and have broad prospects in applications such as electronic devices.
[0149] From the comparison of Examples 1 to 4, it can be seen that as the thickness of the diamond layer increases, the thermal conductivity shows an increasing trend. When the diamond layer is 0.5 mm, the thermal conductivity of the aluminum nitride ceramic reaches a maximum value of 210.8 (W·m -1 ·K -1 ). This is because the thermal conductivity of diamond itself is extremely high. The more diamond content, the greater the thermal conductivity. However, in practical applications in the fields of electronic devices, since the linear expansion coefficient of diamond is smaller than that of semiconductors such as silicon, mechanical failure is prone to occur. Therefore, it is better to control the mass ratio of diamond and aluminum nitride mixture within the above range.
[0150] In addition, it can be seen from the comparison of Examples 1, 8 to 9 that the content of yttrium oxide additives also affects the density and thermal conductivity of aluminum nitride ceramics. As the content of additives increases, the density and thermal conductivity of aluminum nitride ceramics first show an upward trend. When the additive is added in excess (the required total mass is 5wt%), the density and thermal conductivity decrease instead. This may be caused by the following reasons: when the additive content is small, that is, 1wt% of the total mass, the aluminum oxide film on the surface of aluminum nitride cannot fully react with yttrium oxide, and oxygen atoms enter the aluminum nitride lattice to affect phonon scattering, resulting in lower thermal conductivity of aluminum nitride. At the same time, less liquid phase is produced, which affects the density of aluminum nitride. When the additive content is too much, there is too much liquid phase, and the second phase cannot migrate from the grain boundary in time, resulting in a decrease in thermal conductivity.
[0151] In addition, it can be seen from the comparison of Examples 1, 5-7, 9-10 that compared with the method of preparing aluminum nitride ceramics by directly mixing raw materials, the method of layering diamond powder in the present invention has better performance, especially the five-layer structure of the green blank has better thermal conductivity. This is mainly because too many layers are not conducive to the migration of the secondary phase, which in turn affects the improvement of thermal conductivity.
[0152] After the diamond powder is layered, the change in sintering will also affect the final thermal conductivity of the aluminum nitride ceramic. From the comparison of Examples 1 and 13 to 18, it can be seen that the performance of the aluminum nitride ceramic is declining due to the excessively fast heating rate during sintering, the low temperature during the reaction, and the short insulation time. This is mainly because the inappropriate reaction conditions cannot ensure the full reaction of the additive with alumina.
[0153] According to the disclosure and teaching of the above description, those skilled in the art to which the present invention belongs can also change and modify the above embodiment. Therefore, the present invention is not limited to the above specific embodiment, and any obvious improvement, replacement or modification made by those skilled in the art on the basis of the present invention belongs to the protection scope of the present invention. In addition, although some specific terms are used in this specification, these terms are only for the convenience of description and do not constitute any limitation to the present invention.
Claims
1. An aluminum nitride ceramic, characterized in that: The invention comprises an aluminum nitride mixture and diamond, wherein the aluminum nitride mixture comprises aluminum nitride and yttrium oxide, wherein the mass ratio of the aluminum nitride mixture to the diamond is (12-18):(1.6-4), and the mass content of yttrium oxide is 1%-5% of the total mass of the aluminum nitride mixture.
2. The aluminum nitride ceramic according to claim 1, characterized in that: The mass ratio of the aluminum nitride mixture to diamond is (12-18):(2.4-3.2); the particle size D50 of the aluminum nitride powder is 1 μm-3 μm, and the particle size D50 of the yttrium oxide powder is 1 μm-3 μm.
3. A method for preparing aluminum nitride ceramics, characterized in that: The following steps are involved: S1, mixing aluminum nitride and yttrium oxide, and pressing to form a first mixed layer; S2, laying diamond powder on the upper surface of the first mixed layer, and pressing to form a first diamond layer; S3, continuing to lay a mixture of aluminum nitride and yttrium oxide on the upper surface of the first diamond layer, and pressing to form a second mixed layer; S4, repeating step S2 and step S3 in sequence, the number of repetitions is 0 to 2 times, to obtain a green billet; S5. Sinter the green blank obtained in step S4 at a pressure of 30 to 50 MPa and a temperature of 1600 to 1850° C. in an inert gas atmosphere for 4 to 8 hours, and then cool the mixture to obtain aluminum nitride ceramics.
4. The method for preparing aluminum nitride ceramics according to claim 3, characterized in that: The pressing pressure of step S1 to step S4 is 30-40 MPa, and the pressing time is 5-10 min. In step S1 to step S4, the total thickness of the diamond layer is 0.4 mm-1 mm, and the total thickness of the mixed layer is 1.6 mm-2.4 mm.
5. The method for preparing aluminum nitride ceramics according to claim 3, characterized in that: Step S4 also includes laying boron nitride powder on both sides of the blank.
6. The method for preparing aluminum nitride ceramics according to claim 3, characterized in that: In step S5, the temperature is heated to 1600° C. to 1850° C. at a heating rate of 10 to 20° C. / min for sintering.
7. The method for preparing aluminum nitride ceramics according to any one of claims 3 to 6, characterized in that: The number of repetitions in step S4 is 1; The preparation steps of the green billet are: Aluminum nitride and yttrium oxide are mixed and pressed to form a first mixed layer; Placing diamond powder on the upper surface of the first mixed layer and pressing to form a first diamond layer; A mixture of aluminum nitride and yttrium oxide is continuously laid on the upper surface of the first diamond layer, and pressed to form a second mixed layer; Diamond powder is laid on the upper surface of the second mixed layer and pressed to form a second diamond layer; A mixture of aluminum nitride and yttrium oxide is continuously laid on the upper surface of the second diamond layer, and pressed to form a third mixed layer to obtain a green blank.
8. The method for preparing aluminum nitride ceramics according to claim 7, characterized in that: The thickness of the first mixed layer after pressing is a, the thickness of the second mixed layer after pressing is b, the thickness of the third mixed layer after pressing is c, the thickness of the first diamond layer after pressing is m, and the thickness of the second diamond layer after pressing is n, satisfying the following relationship: 0<a≤b, 0<c≤b, 0<m≤b, 0<n≤b.
9. The method for preparing aluminum nitride ceramics according to claim 8, characterized in that: The value of m or n is independently selected from 0.2 mm to 0.5 mm, the value of b is 0.8 mm to 1.2 mm, and the value of a or c is independently selected from 0.4 mm to 0.6 mm.
10. Use of the aluminum nitride ceramic according to any one of claims 1 to 2 or the aluminum nitride ceramic prepared by the preparation method of the aluminum nitride ceramic according to any one of claims 3 to 9 in electronic devices.
Citation Information
Patent Citations
Preparation method of aluminum nitride / diamond polycrystalline material
CN112047740A
Ceramic substrate and preparation method thereof
CN115286397A
Low-temperature sintering process of aluminum nitride ceramic material
CN116425551A
Method of manufacturing substrate of high thermal conductivity
JP2002356389A
Method for preparation the surface of ceramic sintereings of aluminum nitride containing yttrium oxide additive
PL401448A1